Subglacial Lake Vostok not expected to discharge water. Issue 19 (6th October 2014) - Richter, Andreas; Popov, Sergey V.; Schröder, Ludwig; Schwabe, Joachim; Ewert, Heiko; Scheinert, Mirko; Horwath, Martin; Dietrich, Reinhard
Abstract The question whether Antarctica's largest lake, subglacial Lake Vostok, exchanges water is of interdisciplinary relevance but has been undecided so far. We present the potential pathway, outlet location, and threshold height of subglacial water discharge from this lake based on a quantitative evaluation of the fluid potential. If water left Lake Vostok, it would flow toward Ross Ice Shelf. Discharge would occur first to the east of the southern tip of the lake. At this location the bedrock threshold is 91 ± 23 m higher than the hydrostatic equipotential level of Lake Vostok. It is concluded that Lake Vostok is not likely to reach this level within climatic timescales and that no discharge of liquid water is to be expected. We show that in absence of the ice sheet the Lake Vostok depression would harbor a lake significantly deeper and larger than the present aquifer.